Functional analysis of cytotoxic cells in patients with acute nonlymphoblastic leukemia in complete remission - Trentin, Livio; Pizzolo, Giovanni; Feruglio, Cristina; Zambello, Renato; Masciarelli, Maria; Bulian, Pietro; Agostini, Carlo; Vinante, Fabrizio; Zanotti, Roberta; Semenzato, Gianpietro (Cancer, 1989)
In the current study, we investigated the cytotoxic ability of peripheral blood mononuclear cells (PBMC) recovered from patients with acute nonlymphoblastic leukemia (ANLL) in complete remission (CR) against natural killer (NK)‐sensitive, NK‐resistant, autologous and allogeneic leukemic target cells taken at diagnosis. Our purpose was to define the role played by cytotoxic mechanisms in the control of leukemic cell growth in ANLL. Experiments were carried out at resting conditions and after in vitro activation with recombinant interleukin‐2 (rIL‐2) and anti‐CD3 monoclonal antibody (moAb). At resting conditions, PBMC recovered from ANLL patients displayed a NK function that was not significantly different from controls (mean ± standard error of the mean [SEM]: 21.9% ± 3.9% versus control values of 27.5% ± 2.9%; the P value was not significant [NS]), but they were unable to show cytotoxic activity against autologous and allogeneic leukemic cells. After in vitro boosting with rIL‐2, PBMC were able to generate lymphokine activated killer (LAK) cells, as demonstrated by an increased killing of NK‐resistant Daudi targets (16.3% ± 2.7%). Although LAK activity was quantitatively lower than in control subjects (mean ± SEM: 16.3% ± 2.7% versus control values of 79.8% ± 3.1%; P < 0.001), it still exerted a cytotoxic effect against autologous and allogeneic leukemic cells. Similar results were obtained when anti‐CD3 moAb was used as a stimulus in vitro. Our data suggest that nonspecific cytotoxic cells may be triggered to exert an in vitro cytotoxic effect on leukemic cells, which could possibly play a key role in vivo in the control of leukemic cell growth regulation.